Light curing film for special-shaped composite material and preparation method of light curing film
By developing a photo-solid film containing multiple functional components for the special-shaped PC composite, the problem that the special-shaped PC composite is difficult to fully cover the surface during the bonding process is solved, and good bonding is achieved and multiple properties of the composite are improved.
Patent Information
- Application Number
- CN202411886591.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-20
AI Technical Summary
It is difficult for the special-shaped PC composite to fully cover the surface during the bonding process, resulting in local curling, wrinkles or unsolid adhesion.
A photo-solid film for a special-shaped composite material is provided, which contains components such as photocuring resin, tackifier, aerogel, flexible toughening agent, ultraviolet photocatalyst, viscosity regulator, nanosilicon, liquid crystal polymer, superhydrophobic material, photo-thermal conversion material and reactive solvent. By curing and spraying the superhydrophobic material through ultraviolet light, a uniform and solid film layer is formed.
The optical solid film achieves good bonding on the surface of the special-shaped substrate, has excellent exhaust properties, rebound resistance, and adapts to complex shapes, solves the problem of difficult bonding, and improves the ultraviolet resistance, thermal stability and corrosion resistance of the composite material.
Smart Images

Figure BDA0005199466190000081 
Figure BDA0005199466190000091 
Figure BDA0005199466190000121
Abstract
Description
Technical Field
[0001] The invention relates to the field of photocurable films, in particular to a photocurable film for special-shaped composite materials and a preparation method thereof. Background Art
[0002] In modern manufacturing, special-shaped composite materials are increasingly used, especially in the automotive, aerospace, electronics, optics and other industries. Polycarbonate (PC) materials, as a polymer material with excellent physical, optical and mechanical properties, are widely used in these fields. Polycarbonate (PC) materials are widely used in automotive exterior parts, electronic equipment housings, optical components and other fields due to their excellent optical properties, impact resistance and heat resistance.
[0003] However, the special-shaped processing and surface treatment of PC materials face a series of technical difficulties, especially when PC materials need to be bonded with other special-shaped composite surfaces. Since PC materials have certain rigidity and surface hardness, and are often complex in shape, the surface contour of special-shaped substrates is often irregular, which makes it difficult for the film material to completely cover the surface during the bonding process, resulting in local warping, wrinkling or loose adhesion. Although there are a variety of film materials and molding processes for composite surface treatment on the market, there is still a lack of a solution that can effectively solve the above-mentioned problems in the bonding of special-shaped PC composite materials. Therefore, the development of a photocurable film specifically for special-shaped PC composite materials and its preparation method has important application value and market demand. Summary of the invention
[0004] The purpose of this section is to address the bonding problem of surface treatment of special-shaped PC composite materials in the prior art, and to provide a photocurable film for special-shaped composite materials and a preparation method thereof. The photocurable film can achieve good bonding on the surface of special-shaped substrates, has excellent air discharge and anti-rebound properties, and can adapt to substrates with complex shapes, thereby solving the bonding difficulty problem in the prior art.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] On the one hand, a photocurable film for a special-shaped composite material is provided, wherein the photocurable film for a special-shaped composite material comprises the following components in weight percentage:
[0007] Light-curing resin 60% to 85%;
[0008] Thickener 1% to 5%;
[0009] Silica aerogel 1% to 3%;
[0010] Flexible toughening agent 2% to 5%;
[0011] Ultraviolet photocatalyst 0.5% to 2%;
[0012] Viscosity modifier 1% to 2%;
[0013] Nano silicon 1% to 3%;
[0014] Liquid crystal polymer (LCP) 5% to 8%;
[0015] Super hydrophobic material 1% to 3%;
[0016] Photothermal conversion materials 0.5% to 1%;
[0017] Reactive solvent 2% to 5%;
[0018] Organic-inorganic composite materials 1% to 3%.
[0019] As a further solution of the present invention: the viscosity of the photocurable resin is in the range of 100-1000 mPa·s, which is used to form a uniform film layer during coating and curing. The wavelength of ultraviolet light for curing the photocurable resin is between 200-400 nm, and the curing time is 1-5 minutes.
[0020] As a further solution of the present invention: the light-curable resin is epoxy resin, acrylic resin or polyurethane resin.
[0021] As a further solution of the present invention: the tackifier is butyl acrylate (BA), octyl acrylate (OctA) or epoxy acrylate, which is used to coat the surface of the special-shaped composite material to form an adjustable viscosity coating, improve the adhesion of the photocurable resin to the surface of the special-shaped composite material, and enhance the adhesion and durability of the film layer.
[0022] As a further solution of the present invention: the flexible toughening agent is polyurethane acrylate (PUA), polyurethane ether (PU Ether), silane acrylate or polyacrylate toughening agent, which is used to improve the flexibility, impact resistance and low and high temperature resistance of the film layer, and prevent the film layer from cracking or deformation under mechanical stress or temperature changes.
[0023] As a further solution of the present invention: the ultraviolet photocatalyst is benzoylethylene (Benzo in), phenyl dibenzophenone (Benzo in) or photoinitiator BAPO. Under ultraviolet light irradiation, the photocatalyst can accelerate the cross-linking reaction of the resin, enhance the curing efficiency, and ensure that the film layer is completely cured in a short time.
[0024] As a further solution of the present invention: the viscosity modifier is hydroxyethyl cellulose (HEC) or polyvinyl pyrrolidone (PVP), which is used to adjust the viscosity of the photocurable resin so as to have better fluidity and lower adhesion during the coating process, ensure uniform coating, and avoid the generation of bubbles or brush marks.
[0025] As a further solution of the present invention: the liquid crystal polymer is polyethylene terephthalate (PET) or liquid crystal polyamide (LCPs), which is used to enhance the thermal stability, mechanical strength and anti-aging performance of the photocurable film and improve the long-term durability of the film layer.
[0026] As a further solution of the present invention: the super hydrophobic material is a fluororesin coating, a fluorosilane trifluorochloroalkylsilane or a nano-silica coating, which gives the film layer strong waterproof and anti-fouling properties, reduces the adhesion of water and oil, and improves the performance of the film layer in wet or harsh environments.
[0027] As a further solution of the present invention: the photothermal conversion material is graphene, which improves the thermal conversion efficiency of the photocurable film under ultraviolet light irradiation, helps to optimize the thermal management of the composite material, and enhances the high temperature resistance of the film layer.
[0028] As a further solution of the present invention: the reactive solvent is butadiene, which acts as a solvent to help dissolve the resin, reduce the viscosity of the photocurable film coating, and facilitate the coating operation.
[0029] As a further solution of the present invention: the organic-inorganic composite material is siloxane, which provides the film layer of the photocurable film with better adhesion and surface modification function, and enhances the chemical corrosion resistance and environmental stability of the film layer.
[0030] Another aspect of the present invention provides a method for preparing a photocurable film of a special-shaped composite material, comprising the following steps:
[0031] Prepare the raw materials according to the weight percentage, add the reactive solvent into the reaction container and heat it to 50-60°C, and add the photocurable resin into the reactive solvent and stir until it is completely dissolved;
[0032] Slowly adding a viscosity modifier to a reaction container, and adding silica aerogel, nano-silicon, liquid crystal polymer and organic-inorganic composite material to the reaction container, and dispersing them by ultrasonic or high-speed stirring to obtain a dispersion;
[0033] Adding a flexible toughening agent to the dispersion and continuing to stir until uniform, adding an ultraviolet catalyst and a photothermal conversion material, stirring evenly, to obtain a photocurable film coating;
[0034] The photocurable film coating is placed in a vacuum degassing device to remove air bubbles by degassing, and the degassed photocurable film coating is evenly coated on the surface of the special-shaped composite material coated with the tackifier;
[0035] The coated composite material is sent into an ultraviolet curing device and cured by ultraviolet light;
[0036] After the curing treatment, the super-hydrophobic material is evenly sprayed on the surface of the cured photocurable film using a spray gun, and heated in a temperature-controlled box until the resin is completely cross-linked. The cured photocurable film is quality inspected and packaged and stored after the inspection is completed.
[0037] As a further solution of the present invention, the photocurable film coating is placed in a vacuum degassing device and degassed for 10-15 minutes.
[0038] As a further embodiment of the present invention, when ultraviolet light is used for curing, the wavelength of the ultraviolet light is in the range of 200-400 nm, and the power of the ultraviolet light is in the range of 200-300 mJ / cm 2 The curing time is 1-5 minutes. Under ultraviolet light, the initiator in the photocurable resin begins to activate, promoting the cross-linking reaction, and the film layer is cured within a few minutes.
[0039] As a further embodiment of the present invention, when the tackifier is coated on the surface of the special-shaped composite material, the tackifier is coated on the surface of the composite material using a coating machine, and the coating amount is 20-50g / m 2 , drying temperature 40-60°C, drying time 1-3 minutes; then the degassed light-cured film coating is evenly coated on the surface of the special-shaped composite material coated with the tackifier.
[0040] As a further embodiment of the present invention, when the super-hydrophobic material is uniformly sprayed on the surface of the cured photocurable film by a spray gun, the coating amount of the super-hydrophobic material is 0.5-5 g / m 2 , the heating temperature is 60-100℃ and the curing time is 20-60 minutes.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] The present invention provides a photocurable film for a special-shaped composite material and a preparation method thereof. The prepared photocurable film significantly improves the surface functionality of the composite material by adding a super-hydrophobic material, a photothermal conversion material, nano-silicon, a liquid crystal polymer (LCP), etc. The photocurable film not only has super-hydrophobicity, effectively resists the attachment of water droplets and stains, and maintains the cleanliness of the composite material, but also can enhance the UV resistance of the composite material and extend its service life. By adopting a liquid crystal polymer (LCP) and an organic-inorganic composite material, the photocurable film has good flexibility and wear resistance, and also exhibits excellent thermal stability and corrosion resistance, and can maintain long-term durability in harsh environments.
[0043] The present invention provides a photocurable film for special-shaped composite materials and a preparation method thereof, which not only has the firmness, durability and environmental protection that a photocurable film should have, but also has multiple functions such as super-hydrophobicity, self-cleaning, photothermal management, etc., and is widely applicable to the surface protection of various special-shaped composite materials. The preparation method is simple, efficient, and highly adaptable, and has broad application prospects, especially in the fields of automobiles, aerospace, construction, electronics, etc., and can greatly improve the performance and service life of composite materials. DETAILED DESCRIPTION
[0044] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below.
[0045] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0046] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0047] Example 1
[0048] The embodiment of the present invention provides a photocurable film for a special-shaped composite material and a preparation method thereof, which are specifically as follows:
[0049] Raw materials preparation:
[0050] Prepare the raw materials according to the following weight percentages:
[0051] Light-curing resin (epoxy resin): 73%;
[0052] Tackifier (butyl acrylate): 3%;
[0053] Silica aerogel: 2%;
[0054] Flexible toughening agent (polyurethane acrylate): 3%;
[0055] UV photocatalyst (benzoylethylene): 1%;
[0056] Viscosity modifier (hydroxyethyl cellulose, HEC): 1.2%;
[0057] Nano silicon: 2%;
[0058] Liquid crystal polymer (polyethylene terephthalate, PET): 6%;
[0059] Super hydrophobic material (fluororesin coating): 2%;
[0060] Photothermal conversion materials (graphene): 0.8%;
[0061] Reactive solvent (butadiene): 4%;
[0062] Organic-inorganic composite material (siloxane): 2%.
[0063] The preparation steps of the photocurable film for special-shaped composite materials are as follows:
[0064] (1) Preparation of reaction solution:
[0065] The reactive solvent butadiene was added into the reaction vessel and heated to 55° C. Then the photocurable resin (urethane acrylate) was added and stirred until it was completely dissolved to form a uniform resin solution.
[0066] (2) Dispersion and homogenization:
[0067] Slowly add viscosity modifier (HEC) to the resin solution, then add silica aerogel, nanosilicon, liquid crystal polymer (PET) and organic-inorganic composite material (siloxane). Use ultrasonic or high-speed stirring equipment to disperse the mixed liquid to ensure that each component is fully and evenly dispersed to obtain a dispersion.
[0068] (3) Add toughening agent and catalyst:
[0069] Add a flexible toughening agent (polyurethane acrylate) to the dispersion and continue to stir until uniform. Then add an ultraviolet light catalyst (benzoylethylene) and a photothermal conversion material (graphene), stir again until uniform, and obtain the final photocurable film coating.
[0070] (4) Degassing and coating:
[0071] Place the photocurable film coating in a vacuum degassing device and degas for 10 minutes to remove bubbles. Then evenly apply the degassed coating on the surface of the special-shaped composite material pre-coated with a tackifier. The tackifier is coated on the composite surface using butyl acrylate (BA) with a coating amount of 40g / m 2 After coating, the drying temperature is 50°C and the drying time is 2 minutes.
[0072] (5) UV curing:
[0073] The coated composite material is sent to the UV curing equipment and irradiated with UV light in the wavelength range of 200-400nm with a UV light power of 250mJ / cm 2 The irradiation time is 3 minutes. The initiator in the photocurable resin is activated under ultraviolet light, promoting the cross-linking reaction, and the film layer is cured in a short time.
[0074] (6) Spraying super hydrophobic material:
[0075] Use a spray gun to evenly spray the fluororesin coating on the surface of the cured light-cured film, with a spraying amount of 2g / m 2 The sprayed composite material is then sent to a temperature-controlled box and heated to 80°C for 30 minutes to ensure that the resin is fully cross-linked.
[0076] (7) Final testing and packaging:
[0077] After curing, the light-cured film is quality inspected to ensure that the film layer is uniform, free of bubbles and cracks. After passing the inspection, the light-cured film is packaged and stored.
[0078] Performance Test:
[0079] Film thickness test: Use a digital thickness gauge to measure the thickness of the photocured film. Randomly select three locations for testing and record the film thickness at each location. The film thicknesses at the three locations are 13.6μm, 13.5μm, and 13.8μm, respectively. The film thickness at each location is within the range of 12-15μm, meeting the design requirements.
[0080] Surface contact angle test: The contact angle of the surface of the photocured film was tested using a contact angle meter to conduct a superhydrophobicity test. The measured contact angle was 160°, indicating that the film layer had very good superhydrophobic properties and could effectively resist water and dirt.
[0081] Mechanical strength and flexibility test: Use a tensile testing machine to perform a tensile test on the light-cured film to test the tensile strength and elongation at break of the film layer. The test results are as follows:
[0082] 1. Tensile strength: 45MPa;
[0083] 2. Elongation at break: 8%.
[0084] The results show that the film layer has good mechanical strength and flexibility, and can effectively resist external force impact.
[0085] Thermal stability test: The thermal stability of the photocured film was tested using a thermogravimetric analysis (TGA) instrument. The results showed that the film quality was stable below 250°C, with a weight loss of less than 5%. This result indicates that the film has good thermal stability.
[0086] Curing efficiency test: The UV light absorption and cross-linking during the curing process were monitored by a UV curing test instrument. The results showed that the curing efficiency was 98%, indicating that the cross-linking reaction of the resin under UV light was very efficient.
[0087] The data table is as follows:
[0088]
[0089]
[0090] The experimental results show that:
[0091] Membrane thickness: meets the design requirements, uniform and bubble-free, with a thickness of 12-15μm; superhydrophobicity: the contact angle reaches 160°, with excellent waterproof and antifouling properties; mechanical strength and flexibility: the tensile strength is 45MPa, the elongation at break is 8%, and it has good flexibility; thermal stability: stable below 250°C, with a weight loss of less than 5%; curing efficiency: the curing efficiency under ultraviolet light reaches 98%, the resin is completely cross-linked, and the film layer is stable.
[0092] The photocured film prepared in this embodiment has excellent super-hydrophobicity, mechanical strength, chemical corrosion resistance and thermal stability, is suitable for surface coating of various special-shaped composite materials, and can effectively improve the performance of composite materials in harsh environments.
[0093] Example 2
[0094] The embodiment of the present invention provides a photocurable film for a special-shaped composite material and a preparation method thereof, which are specifically as follows:
[0095] Raw materials preparation:
[0096] Prepare the raw materials according to the following weight percentages:
[0097] Light-curing resin (acrylic resin): 69%;
[0098] Tackifier (octyl acrylate): 4%;
[0099] Silica aerogel: 3%;
[0100] Flexible toughening agent (polyurethane ether): 4.5%;
[0101] UV photocatalyst (phenyl benzophenone): 1.5%;
[0102] Viscosity modifier (polyvinyl pyrrolidone, PVP): 2%;
[0103] Nano silicon: 1.5%;
[0104] Liquid crystal polymers (liquid crystal polyamides, LCPs): 8%;
[0105] Super hydrophobic material (fluorosilane trifluorochloroalkylsilane): 1.5%;
[0106] Photothermal conversion materials (graphene): 1%;
[0107] Reactive solvent (butadiene): 3%;
[0108] Organic-inorganic composite material (siloxane): 1%.
[0109] The preparation steps of the photocurable film for special-shaped composite materials are as follows:
[0110] (1) Preparation of reaction solution:
[0111] The reactive solvent butadiene was added into the reaction vessel and heated to 60° C. Then the photocurable resin (polyurethane ether) was added and stirred until it was completely dissolved to form a uniform resin solution.
[0112] (2) Dispersion and homogenization:
[0113] Slowly add the viscosity modifier (polyvinyl pyrrolidone) to the resin solution, then add silica aerogel, nanosilicon, liquid crystal polymer (liquid crystal polyamide) and organic-inorganic composite material (siloxane). Use ultrasonic or high-speed stirring equipment to disperse the mixed liquid to ensure that each component is fully and evenly dispersed to obtain a dispersion.
[0114] (3) Add toughening agent and catalyst:
[0115] Add a flexible toughening agent (polyurethane ether) to the dispersion and continue to stir evenly. Then add an ultraviolet light catalyst (phenyl benzophenone) and a photothermal conversion material (graphene), stir again until evenly mixed, and obtain the final photocurable film coating.
[0116] (4) Degassing and coating:
[0117] Place the photocurable film coating in a vacuum degassing device and degas for 15 minutes to remove bubbles. Then evenly apply the degassed coating on the surface of the special-shaped composite material that has been pre-coated with a tackifier. Octyl acrylate (OctA) is used as the tackifier and applied on the composite surface at a coating amount of 50 g / m 2 After coating, the drying temperature is 60°C and the drying time is 3 minutes.
[0118] (5) UV curing:
[0119] The coated composite material is sent to the UV curing equipment and irradiated with UV light in the wavelength range of 200-400nm with a UV light power of 300mJ / cm 2 , the irradiation time is 1 minute. The initiator in the photocurable resin is activated under ultraviolet light, promoting the cross-linking reaction, and the film layer is cured in a short time.
[0120] (6) Spraying super hydrophobic material:
[0121] Use a spray gun to evenly spray fluorosilane trifluorochloroalkylsilane on the surface of the cured light-cured film, with a spraying amount of 5g / m 2 The sprayed composite material is then sent to a temperature-controlled box and heated to 100°C for 20 minutes to ensure that the resin is fully cross-linked.
[0122] (7) Final testing and packaging:
[0123] After curing, the light-cured film is quality inspected to ensure that the film layer is uniform, free of bubbles and cracks. After passing the inspection, the light-cured film is packaged and stored.
[0124] Performance Test:
[0125] Film thickness test: Use a digital thickness gauge to measure the thickness of the photocured film. Randomly select three locations for testing and record the film thickness at each location. The film thicknesses at the three locations are 12.5μm, 13.1μm and 12.7μm, respectively. The film thickness at each location is within the range of 12-15μm, meeting the design requirements.
[0126] Surface contact angle test: The contact angle of the surface of the photocured film was tested using a contact angle meter to conduct a superhydrophobicity test. The measured contact angle was 158°, indicating that the film layer had very good superhydrophobic properties and could effectively resist water and dirt.
[0127] Mechanical strength and flexibility test: Use a tensile testing machine to perform a tensile test on the light-cured film to test the tensile strength and elongation at break of the film layer. The test results are as follows:
[0128] 1. Tensile strength: 50MPa;
[0129] 2. Elongation at break: 10%.
[0130] The results show that the film layer has good mechanical strength and flexibility, and can effectively resist external force impact.
[0131] Thermal stability test: The thermal stability of the photocured film was tested using a thermogravimetric analysis (TGA) instrument. The results showed that the film quality was stable below 250°C, with a weight loss of less than 5%. This result indicates that the film has good thermal stability.
[0132] Curing efficiency test: The UV light absorption and cross-linking during the curing process were monitored by a UV curing test instrument. The results showed that the curing efficiency was 96%, indicating that the cross-linking reaction of the resin under UV light was very efficient.
[0133] The data table is as follows:
[0134]
[0135]
[0136] The experimental results show that:
[0137] Membrane thickness: meets the design requirements, uniform and bubble-free, with a thickness of 12-15μm; superhydrophobicity: the contact angle reaches 158°, with excellent waterproof and antifouling properties; mechanical strength and flexibility: the tensile strength is 50MPa, the elongation at break is 10%, and it has good flexibility; thermal stability: stable below 250°C, with a weight loss of less than 5%; curing efficiency: the curing efficiency under ultraviolet light reaches 96%, the resin is completely cross-linked, and the film layer is stable.
[0138] The photocured film prepared in this embodiment has excellent mechanical properties, superhydrophobicity, corrosion resistance and thermal stability, and can be widely used in surface coatings of special-shaped composite materials to improve the durability and functionality of composite materials in extreme environments.
[0139] Example 3
[0140] The embodiment of the present invention provides a photocurable film for a special-shaped composite material and a preparation method thereof, which are specifically as follows:
[0141] Raw materials preparation:
[0142] Prepare the raw materials according to the following weight percentages:
[0143] Light-curing resin (polyurethane resin): 74%;
[0144] Tackifier (epoxy acrylate): 5%;
[0145] Silica aerogel: 1%;
[0146] Flexible toughening agent (silane acrylate): 2%;
[0147] UV photocatalyst (photoinitiator BAPO): 0.5%;
[0148] Viscosity modifier (polyvinyl pyrrolidone, PVP): 1%;
[0149] Nano silicon: 3%;
[0150] Liquid crystal polymers (liquid crystal polyamides, LCPs): 5%;
[0151] Super hydrophobic material (nano-silica coating): 3%;
[0152] Photothermal conversion material (graphene): 0.5%;
[0153] Reactive solvent (butadiene): 2%;
[0154] Organic-inorganic composite material (siloxane): 3%.
[0155] The preparation steps of the photocurable film for special-shaped composite materials are as follows:
[0156] (1) Preparation of reaction solution:
[0157] The reactive solvent butadiene was added into the reaction vessel and heated to 50° C. Then the photocurable resin (silyl acrylate) was added and stirred until it was completely dissolved to form a uniform resin solution.
[0158] (2) Dispersion and homogenization:
[0159] Slowly add the viscosity modifier (polyvinyl pyrrolidone) to the resin solution, then add silica aerogel, nanosilicon, liquid crystal polymer (liquid crystal polyamide) and organic-inorganic composite material (siloxane). Use ultrasonic or high-speed stirring equipment to disperse the mixed liquid to ensure that each component is fully and evenly dispersed to obtain a dispersion.
[0160] (3) Add toughening agent and catalyst:
[0161] Add a flexible toughening agent (silane acrylate) to the dispersion and continue to stir until uniform. Then add an ultraviolet light catalyst (photoinitiator BAPO) and a photothermal conversion material (graphene), stir again until uniform, and obtain the final photocurable film coating.
[0162] (4) Degassing and coating:
[0163] Place the light-curing film coating in a vacuum degassing device and degas for 10 minutes to remove bubbles. Then evenly apply the degassed coating on the surface of the special-shaped composite material that has been pre-coated with a tackifier. The tackifier is applied on the surface of the composite material using epoxy acrylate at a coating amount of 35g / m 2 After coating, the drying temperature is 40°C and the drying time is 3 minutes.
[0164] (5) UV curing:
[0165] The coated composite material is sent to the UV curing equipment and irradiated with UV light in the wavelength range of 200-400nm with a UV light power of 200mJ / cm 2 The irradiation time is 5 minutes. The initiator in the photocurable resin is activated under ultraviolet light, promoting the cross-linking reaction, and the film layer is cured in a short time.
[0166] (6) Spraying super hydrophobic material:
[0167] Use a spray gun to evenly spray the nano-silicon dioxide coating on the surface of the cured light-cured film, with a spraying amount of 0.5g / m 2 The sprayed composite material is then sent to a temperature-controlled box and heated to 60°C for 60 minutes to ensure that the resin is fully cross-linked.
[0168] (7) Final testing and packaging:
[0169] After curing, the light-cured film is quality inspected to ensure that the film layer is uniform, free of bubbles and cracks. After passing the inspection, the light-cured film is packaged and stored.
[0170] Performance Test:
[0171] Film thickness test: Use a digital thickness gauge to measure the thickness of the photocured film. Randomly select three locations for testing and record the film thickness at each location. The film thicknesses at the three locations are 14.1μm, 13.9μm, and 13.8μm, respectively. The film thickness at each location is within the range of 12-15μm, meeting the design requirements.
[0172] Surface contact angle test: The contact angle of the surface of the photocured film was tested using a contact angle meter to conduct a superhydrophobicity test. The measured contact angle was 162°, indicating that the film layer had very good superhydrophobic properties and could effectively resist water and dirt.
[0173] Mechanical strength and flexibility test: Use a tensile testing machine to perform a tensile test on the light-cured film to test the tensile strength and elongation at break of the film layer. The test results are as follows:
[0174] 1.Tensile strength: 48MPa;
[0175] 2. Elongation at break: 9%.
[0176] The results show that the film layer has good mechanical strength and flexibility, and can effectively resist external force impact.
[0177] Thermal stability test: The thermal stability of the photocured film was tested using a thermogravimetric analysis (TGA) instrument. The results showed that the film quality was stable below 250°C, with a weight loss of less than 5%. This result indicates that the film has good thermal stability.
[0178] Curing efficiency test: The UV light absorption and cross-linking during the curing process were monitored by a UV curing test instrument. The results showed that the curing efficiency was 97%, indicating that the cross-linking reaction of the resin under UV light was very efficient.
[0179] The data table is as follows:
[0180]
[0181] The experimental results show that:
[0182] Membrane thickness: meets the design requirements, uniform and bubble-free, with a thickness of 12-15μm; superhydrophobicity: the contact angle reaches 162°, with excellent waterproof and antifouling properties; mechanical strength and flexibility: the tensile strength is 48MPa, the elongation at break is 9%, and it has good flexibility; thermal stability: stable below 250°C, with a weight loss of less than 5%; curing efficiency: the curing efficiency under ultraviolet light reaches 97%, the resin is completely cross-linked, and the film layer is stable.
[0183] The photocured film prepared in this embodiment has excellent mechanical properties, superhydrophobicity, corrosion resistance and thermal stability, and can be widely used in surface coatings of special-shaped composite materials to improve the durability and functionality of composite materials in extreme environments.
[0184] Example 4
[0185] The embodiment of the present invention provides a photocurable film for a special-shaped composite material and a preparation method thereof, which are specifically as follows:
[0186] Raw materials preparation:
[0187] Prepare the raw materials according to the following weight percentages:
[0188] Light-curing resin (acrylic resin): 68%;
[0189] Tackifier (octyl acrylate): 3%;
[0190] Silica aerogel: 2%;
[0191] Flexible toughening agent (polyacrylate toughening agent): 4%;
[0192] UV photocatalyst (photoinitiator BAPO): 2%;
[0193] Viscosity modifier (hydroxyethyl cellulose, HEC): 1%;
[0194] Nano silicon: 2%;
[0195] Liquid crystal polymer (polyethylene terephthalate): 7%;
[0196] Super hydrophobic material (fluorosilane trifluorochloroalkylsilane): 5%;
[0197] Photothermal conversion materials (graphene): 1%;
[0198] Reactive solvent (butadiene): 3%;
[0199] Organic-inorganic composite material (siloxane): 2%.
[0200] The preparation steps of the photocurable film for special-shaped composite materials are as follows:
[0201] (1) Preparation of reaction solution:
[0202] The reactive solvent butadiene was added into the reaction vessel and heated to 55° C. Then the photocurable resin (polyacrylate toughening agent) was added and stirred until it was completely dissolved to form a uniform resin solution.
[0203] (2) Dispersion and homogenization:
[0204] Slowly add the viscosity modifier (polyvinyl pyrrolidone) to the resin solution, then add silica aerogel, nanosilicon, liquid crystal polymer (liquid crystal polyamide) and organic-inorganic composite material (siloxane). Use ultrasonic or high-speed stirring equipment to disperse the mixed liquid to ensure that each component is fully and evenly dispersed to obtain a dispersion.
[0205] (3) Add toughening agent and catalyst:
[0206] Add a flexible toughening agent (polyacrylate toughening agent) to the dispersion and continue to stir evenly. Then add an ultraviolet light catalyst (photoinitiator BAPO) and a photothermal conversion material (graphene), stir again until evenly mixed, and obtain the final photocurable film coating.
[0207] (4) Degassing and coating:
[0208] Place the light-curing film coating in a vacuum degassing device and degas for 15 minutes to remove bubbles. Then evenly apply the degassed coating on the surface of the special-shaped composite material that has been pre-coated with a tackifier. The tackifier is applied on the surface of the composite material using octyl acrylate at a coating amount of 45g / m 2After coating, the drying temperature is 50°C and the drying time is 2 minutes.
[0209] (5) UV curing:
[0210] The coated composite material is sent to the UV curing equipment and irradiated with UV light in the wavelength range of 200-400nm with a UV light power of 250mJ / cm 2 The irradiation time is 3 minutes. The initiator in the photocurable resin is activated under ultraviolet light, promoting the cross-linking reaction, and the film layer is cured in a short time.
[0211] (6) Spraying super hydrophobic material:
[0212] Use a spray gun to evenly spray fluorosilane trifluorochloroalkylsilane on the surface of the cured light-cured film, with a spraying amount of 4g / m 2 The sprayed composite material is then sent to a temperature-controlled box and heated to 80°C for 40 minutes to ensure that the resin is fully cross-linked.
[0213] (7) Final testing and packaging:
[0214] After curing, the light-cured film is quality inspected to ensure that the film layer is uniform, free of bubbles and cracks. After passing the inspection, the light-cured film is packaged and stored.
[0215] Performance Test:
[0216] Film thickness test: Use a digital thickness gauge to measure the thickness of the photocured film. Randomly select three locations for testing and record the film thickness at each location. The film thicknesses at the three locations are 13.8μm, 13.5μm, and 13.6μm, respectively. The film thickness at each location is within the range of 12-15μm, meeting the design requirements.
[0217] Surface contact angle test: The contact angle of the surface of the photocured film was tested using a contact angle meter to conduct a superhydrophobicity test. The measured contact angle was 160°, indicating that the film layer had very good superhydrophobic properties and could effectively resist water and dirt.
[0218] Mechanical strength and flexibility test: Use a tensile testing machine to perform a tensile test on the light-cured film to test the tensile strength and elongation at break of the film layer. The test results are as follows:
[0219] 1. Tensile strength: 50MPa;
[0220] 2. Elongation at break: 10%.
[0221] The results show that the film layer has good mechanical strength and flexibility, and can effectively resist external force impact.
[0222] Thermal stability test: The thermal stability of the photocured film was tested using a thermogravimetric analysis (TGA) instrument. The results showed that the film quality was stable below 250°C, with a weight loss of less than 5%. This result indicates that the film has good thermal stability.
[0223] Curing efficiency test: The UV light absorption and cross-linking during the curing process were monitored by a UV curing test instrument. The results showed that the curing efficiency was 98%, indicating that the cross-linking reaction of the resin under UV light was very efficient.
[0224] The data table is as follows:
[0225]
[0226] The experimental results show that:
[0227] Membrane thickness: meets the design requirements, uniform and bubble-free, with a thickness of 12-15μm; superhydrophobicity: the contact angle reaches 160°, with excellent waterproof and antifouling properties; mechanical strength and flexibility: the tensile strength is 50MPa, the elongation at break is 10%, and it has good flexibility; thermal stability: stable below 250°C, with a weight loss of less than 5%; curing efficiency: the curing efficiency under ultraviolet light reaches 98%, the resin is completely cross-linked, and the film layer is stable.
[0228] The photocured film prepared in this embodiment has excellent mechanical properties, superhydrophobicity, corrosion resistance and thermal stability, and can be widely used in surface coatings of special-shaped composite materials to improve the durability and functionality of composite materials in extreme environments.
[0229] In summary, through the above four embodiments, it can be clearly seen that the photocurable film for special-shaped composite materials of the present invention significantly improves the surface functionality of the composite material by adding super-hydrophobic materials, photothermal conversion materials, nano-silicon, liquid crystal polymers (LCP), etc. The photocurable film not only has super-hydrophobicity, effectively resists the attachment of water droplets and stains, maintains the cleanliness of the composite material, but also can enhance the UV resistance of the composite material, prolong its service life, and by adopting liquid crystal polymers (LCP) and organic-inorganic composite materials, the photocurable film has good flexibility and wear resistance, and also exhibits excellent thermal stability and corrosion resistance, and can maintain long-term durability in harsh environments.
[0230] Importantly, it should be noted that the construction and arrangement of the present application shown in a plurality of different exemplary embodiments are only exemplary. Although only a few embodiments are described in detail in this disclosure, it should be readily understood by those who refer to this disclosure that many modifications are possible (e.g., the size, scale, structure, shape and proportion of various elements, and parameter values (e.g., temperature, pressure, etc.), installation arrangement, use of materials, color, directional changes, etc.) without substantially departing from the novel teachings and advantages of the subject matter described in the application. For example, the element shown as integrally formed can be composed of multiple parts or elements, the position of the element can be inverted or otherwise changed, and the nature or number or position of the discrete element can be changed or changed. Therefore, all such modifications are intended to be included in the scope of the present invention. The order or sequence of any process or method steps can be changed or reordered according to alternative embodiments. In the claims, any "device plus function" clause is intended to cover the structure of performing the function described herein, and is not only structurally equivalent but also equivalent structure. Without departing from the scope of the present invention, other replacements, modifications, changes and omissions can be made in the design, operating conditions and arrangement of the exemplary embodiments. Therefore, the invention is not limited to a specific embodiment, but extends to numerous modifications still falling within the scope of the appended claims.
[0231] Additionally, in order to provide a concise description of exemplary embodiments, all features of an actual embodiment (ie, those features that are not relevant to the best mode presently contemplated for carrying out the invention or those that are not relevant to implementing the invention) may not be described.
[0232] It will be appreciated that in the development of any actual implementation, as in any engineering or design project, numerous implementation-specific decisions may be made. Such a development effort may be complex and time-consuming, but will be a routine task of design, fabrication, and production for those of ordinary skill having the benefit of this disclosure without undue experimentation.
[0233] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A photocurable film for a special-shaped composite material, characterized in that: The photocurable film for special-shaped composite materials comprises the following components in percentage by weight: Light-curing resin 60% to 85%; Thickener 1% to 5%; Silica aerogel 1% to 3%; Flexible toughening agent 2% to 5%; Ultraviolet photocatalyst 0.5% to 2%; Viscosity modifier 1% to 2%; Nano silicon 1% to 3%; Liquid crystal polymer 5% to 8%; Super hydrophobic material 1% to 3%; Photothermal conversion materials 0.5% to 1%; Reactive solvent 2% to 5%; Organic-inorganic composite materials 1% to 3%.
2. The photocurable film for special-shaped composite materials according to claim 1, characterized in that: The viscosity of the photocurable resin is in the range of 100-1000 mPa·s, and is used to form a uniform film layer during coating and curing. The wavelength of ultraviolet light for curing the photocurable resin is between 200-400 nm, and the curing time is 1-5 minutes.
3. The photocurable film for special-shaped composite materials according to claim 2, characterized in that: The light-curable resin is epoxy resin, acrylic resin or polyurethane resin.
4. The photocurable film for special-shaped composite materials according to claim 1, characterized in that: The tackifier is butyl acrylate, octyl acrylate or epoxy acrylate, and is used for coating on the surface of the special-shaped composite material to form a coating with adjustable viscosity.
5. The photocurable film for special-shaped composite materials according to claim 1, characterized in that: The flexible toughening agent is polyurethane acrylate, polyurethane ether, silane acrylate or polyacrylate toughening agent; the ultraviolet light catalyst is benzoylethylene, phenyl benzophenone or photoinitiator BAPO; the viscosity modifier is hydroxyethyl cellulose or polyvinyl pyrrolidone.
6. The photocurable film for special-shaped composite materials according to claim 1, characterized in that: The liquid crystal polymer is polyethylene terephthalate or liquid crystal polyamide; the super hydrophobic material is a fluororesin coating, a fluorosilane trifluorochloroalkylsilane or a nano silicon dioxide coating.
7. The photocurable film for special-shaped composite materials according to claim 1, characterized in that: The photothermal conversion material is graphene; the reactive solvent is butadiene; and the organic-inorganic composite material is siloxane.
8. A method for preparing a photocurable film for a special-shaped composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Prepare the raw materials according to the weight percentage, add the reactive solvent into the reaction container and heat it to 50-60°C, and add the photocurable resin into the reactive solvent and stir until it is completely dissolved; Slowly adding a viscosity modifier to a reaction container, and adding silica aerogel, nano-silicon, liquid crystal polymer and organic-inorganic composite material to the reaction container, and dispersing them by ultrasonic or high-speed stirring to obtain a dispersion; Adding a flexible toughening agent to the dispersion and continuing to stir until uniform, adding an ultraviolet catalyst and a photothermal conversion material, stirring evenly, to obtain a photocurable film coating; The photocurable film coating is placed in a vacuum degassing device to remove air bubbles by degassing, and the degassed photocurable film coating is evenly coated on the surface of the special-shaped composite material coated with the tackifier; The coated composite material is sent into an ultraviolet curing device and cured by ultraviolet light; After the curing treatment, the super-hydrophobic material is evenly sprayed on the surface of the cured photocurable film using a spray gun, and heated in a temperature-controlled box until the resin is completely cross-linked. The cured photocurable film is quality inspected and packaged and stored after the inspection is completed.
9. The method for preparing a photocurable film according to claim 8, characterized in that: Place the photocurable film coating into a vacuum degassing device and degas for 10-15 minutes.
10. The method for preparing a photocurable film according to claim 9, characterized in that: When using UV light for curing, the UV wavelength range is 200-400nm and the UV power is 200-300mJ / cm 2 , the curing time is 1-5 minutes.
Citation Information
Patent Citations
Organic-inorganic hybridization ultraviolet cured paint for protecting metallic surface
CN101307194A
Organic-inorganic hybridization coating cured by photothermal for protecting metallic surface
CN101338086A
Graphene-based photocurable coating and preparation method thereof
CN106189418A
Hydrophobic coating layer for substrate and preparation method thereof
CN106905811A
Epoxy resin coating reinforced by polyethylene glycol terephthalate crystal and preparation method thereof
CN114316744A